Sistem Pakar pada Sistem Pembayaran Uang Kuliah Cicilan Menggunakan Metode Weighted Product (Studi Kasus Universitas Dharma Andalas) - Rahmad Supriadi; Gunadi Widi Nurcahyo (SEULANGA SYSTEM PUBLISHER, 2021)
Dharma Andalas University is a change in form from the Dharma Andalas Higher School of Economics (STIE). Dharma Andalas University is one of the private universities in the city of Padang which is under the auspices of the Andalas Dharma Education Foundation (YPDA) which is directly fostered by the Andalas University alumni association. Dharma Andalas University is a private university so operational costs come from student tuition fees. Payment of tuition fees is an obligation of every student, considering that tuition fees are quite expensive, Dharma Andalas University provides relief for students to make tuition payments in installments. The purpose of this study is to assist the leadership in making a decision to pay installments using the Weighted Product method. In this study, the data processed is the data of students who apply for installment tuition payments at Dharma Andalas University. The data processing is to determine the criteria for each alternative by multiplying for attribute match reting, then rank with the attribute weight value which results in the vector value V, then the vector value V is ranked from the highest value to the lowest value where the highest value will be prioritized. Furthermore compared to the manual calculation method with a system that has been made, the results are the same with an accuracy rate of 97%, so that it can be recommended to the leadership to help make decisions about the payment of tuition installments.